Memory, Subjective Memory and Motor Functioning in Non-Demented Elders With and Without Parkinson’s Disease - Maria Chiara Fastame; Paul Kenneth Hitchcott; Federica Corona; Giuseppina Pilloni; Micaela Porta; Massimiliano Pau; Maria Pietronilla Penna (Europe's Journal of Psychology, 2019)
Parkinson’s Disease (PD) is a progressive neurological condition characterized by motor and non-motor symptoms impacting life quality. The main aim of the current study was to investigate the effect of PD on objective (i.e., working memory and semantic memory) and subjective memory (i.e., self-reported seriousness of forgetting, mnemonic usage and actual memory efficiency) controlling for the effect of depressive symptomatology. The relationship of working memory performance to gait and mobility indices was also examined, as well as the factors predicting subjective memory were explored. Fifty-four community-dwelling adults (mean age = 72.3 years, SD = 8.8) were recruited in Sardinia, an Italian island located in the Mediterranean Sea. Specifically, 27 non-demented adults with mild, early-stage PD were matched for years of education, age, and gender with a sample of healthy individuals. Participants completed a test battery assessing objective memory, subjective memory, and depressive symptoms, and an instrumental analysis of gait and functional mobility was performed. Participants with PD had poorer objective memory across all indices measured and displayed a restricted set of gait and posture impairments. Working memory performance was selectively related to gait and posture measures. Moreover, participants with PD had lower trust in their memory efficiency relative to the past than the control healthy group. Finally, 22% of the variance in seriousness of the consequences of forgetting was predicted by education and general cognitive efficiency. Overall, the present findings confirm the presence of changes in both objective and subjective memory in PD, independent from depressive symptoms.